Changes in Social Interaction during Covid-19 Pandemic - Yoshida, Shoya (Journal of Asian Multicultural Research for Social Sciences Study, 2020)
This article aims to review social interactions during the covid-19 pandemic. Communication is the process of delivering messages to someone, so that messages can be received and understood. Social contact during a pandemic is divided into contacts between individuals, between groups, and between individuals and groups. Based on actions or responses, interaction is divided into positive and negative social contacts. In the future, society will be faced with a situation of change that was never imagined before. A number of old values and norms must be restructured and reproduced again to produce a new social system.